(English) Dreams Versus (Hebrew) Reality: Henry Roth's Call it Sleep as 'Jewish-American Minor Literature'. (23rd August 2021) - Zuckerstatter, Shiri
Abstract: This article examines Henry Roth's Call It Sleep as a particular example of minor literature written in America while suggesting a new term: 'Jewish-American minor literature'. It has been argued that Jewish-American literature is not minor literature in Gilles Deleuze and Felix Guattari's terms mainly due to the openness of American English to other ethnic languages such as Yiddish. 1 However, this article shows that it is Hebrew, and not Yiddish, that functions as 'minor language' in the text—both as a language spoken by a minority and according to Deleuze and Guattari's concept, as it undermines the theme of linguistic assimilation governing the surface structure of the book. Yet this 'subversive' Hebrew is neither transcribed/transliterated in the text, nor is it referred to or talked about in the novel. Rather, it is 'hidden' behind the English lines of the book. In fact, it is the emerging of such 'concealed' Hebrew hollowing out the idea of Americanisation in the text that turns Call It Sleep into what I call 'Jewish-American minor literature'. 2 Inviting further research, this article may open the door for a new research field investigating (whether there are any) other appearances of covert Hebrew words in additional Jewish-American works written exclusively in English and whether these works too can be considered as 'Jewish-American minor literature'.